O uso de MC em uma abordagem Socio-interacionista no ensino de Física - Lopes, Luis Fernando [UNESP] (2015)
The research presented had as its starting point the teacher's experience in SISTEMA SESI-SP DE ENSINO, which acts as pedagogical technical analyst and had the first contacts with the social-interactional model adopted as a pedagogical framework in . The proposal was to perform a job to help teachers in organizing the content and differentiated assessment of the students through the use of Concept Maps (MC). This tool is a knowledge representation which aids in significant learning and allows the student to assess the progress of a given concept. It is also a potentially useful tool in the analysis of curriculum content on an interactionist social perspective. To contribute to the formation of the teacher who serves on SESI in the second half of 2013, it was proposed to four teachers of high school physics, based in West Paulista crowded region, respectively, in the cities of Assis,Alvares Machado, Santo Anastácio and President Prudente, the insertion work of conceptual maps in their classes under the aegis of methodological procedures SISTEMA SESI-SP DE ENSINO through the use of Cmap Tools software. There was training in the form of workshops in loco and partnership pedagogical technical analyst - teacher for teacher training. As a result it can be concluded that students showed greater willingness to systematize their knowledge and increase their performance in internal evaluations carried out taking into account the use of conceptual map, showing that working with grounded conceptual maps initially on CognitivismAusubel and modeled the perspective of socio-interactionist model, helps both the teacher and the student in the teaching-learning process